Multi-Stability in Low-Symmetry Magnetic Nanoparticles - Altbir-Drullinsky, D; Allende-Prieto, S; Escobar-Donoso, R; Castillo-Sepulveda, S (American Institute of Physics, 2015)
The occurrence of equilibrium magnetic configurations in ferromagnetic low-symmetry nanoparticles has been investigated. T-shaped nanoparticles, which present strong configurational anisotropy, have been considered. It has been found that such particles exhibit four equilibrium magnetic states, whose stability at room temperature was estimated. The presence of structural imperfections, such as surface roughness, in those systems was also considered, resulting in no significant effects on the magnetic behavior of the particles. The present results are expected to be of relevance to magnetic storage. © 2015 AIP Publishing LLC.